Analysis of Free Fatty Acid Contents (As Acid Laurat) Pure Coconut Oil (Virgin Coconut Oil /VCO) which Circulates in Kediri City - Sri Rahayu Dwi Purnaningtyas (Universitas STRADA Indonesia, 2022)
Pure Coconut Oil (Virgin Coconut Oil / VCO) is a vegetable oil that contains medium chain saturated fatty acids. The medium-chain saturated fatty acid that has the highest content in virgin coconut oil is lauric acid. Lauric acid can be directly absorbed by the liver and used as an energy source. This study aims to determine the levels of free fatty acids (as lauric acid) in virgin coconut oil (Virgin Coconut Oil/VCO) according to SNI Standard 7381: 2008. The samples used in this study were pure coconut oil from various brands on the market in Indonesia. Kediri city. This study used an alkalimetry method to identify the free fatty acid levels in the sample. From the results of the analysis on 5 (five) brands of virgin coconut oil, it was found that all samples met the requirements of SNI 7381: 2008 which is a maximum of 0.2%. The results of the analysis of the levels of free fatty acids as lauric acid, the largest 0.1988% and the smallest 0.1643% according to the requirements of SNI.